105k views
4 votes

solve : - \\ \\ (10 {}^(2) - 6 {}^(2) ) = {?}


2 Answers

6 votes
The answer will be 64
User QuestionC
by
4.4k points
5 votes


\longrightarrow{\blue{64}}


\large\mathfrak{{\pmb{\underline{\orange{Step-by-step\:explanation}}{\orange{:}}}}}


= (10 {}^(2) - 6 {}^(2) )


= [(10 * 10) - (6 * 6)]


= (10 0- 36)


= 64


\red{\large\qquad \qquad \underline{ \pmb{{ \mathbb{ \maltese \: \: Mystique35ヅ}}}}}

User Sovanesyan
by
4.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.